Peran strategi promosi dan produk spesial mingguan dalam meningkatkan penjualan pada Alfamart Villa Nusa Indah 7 - Shaoqi, Rifqi; Wijayanti, Rini (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2026)
This study aims to analyze the role of promotional strategies and weekly special products in increasing sales at Alfamart Villa Nusa Indah 7. The research method used is qualitative through observation, interviews, and documentation. The results show that promotional strategies, including advertising, sales promotion, public relations, and personal selling, are proven to play a role in increasing sales, while the weekly special product program also contributes to increasing consumer purchases and customer loyalty. Thus, promotional strategies and weekly special products play an important role in supporting the achievement of store sales targets.